HUBUNGAN PENDIDIKAN DAN PARITAS IBU TERHADAP PEMILIHAN KB DI PUSKESMAS BANJAR II BULELENG BALI - Lala Fitriana; Anita Liliana; Ida Ayu Deva Wulandari (Indonesian National Nurses Association (INNA) of Central Java, 2022)
KB is used to improve the welfare of mothers and children in order to realize the norms of small families happy prosperous which is the basis of the realization of a prosperous society by promoting birth while ensuring the control of the population. The higher the level of education the more rational the decision-making, one of which is in the use of kb. Parity can affect a person's birth control because the more children are born, the higher the mother's desire to limit birth. This condition will encourage a mother to use birth control. To know the education and parity of the mother to the election of KB in Banjar Health center II Buleleng Bali. This type of research is quantitative with cross sectional design. The study was conducted in July 2020 with a total sample of 236 respondents. Sampling techniques using total sampling. Research instruments use observation sheets. Analyze data using Chi square. The results of the education univariate test surveyed 162 respondents (68.6%), multipara parity 187 respondents (79.2%), hormonal KB 227 respondents (96.2%), age ≤30 ≥30 years 118 respondents (50.0%), not working 142 respondents (60.2%). Educational bivariate test results with KB show p value of 1,000 and parity with KB shows p value 0.947. No education relations and parity of the election of the KB in Banjar Health center II Buleleng Bali.